Decomposing poverty in hard times: Greece 2007-2016 - Eirini Andriopoulou; Eleni Kanavitsa; Panos Tsakloglou (Global Labor Organization (GLO), 2020)
The Greek economic crisis resulted in a decline in household disposable income by more than 40%. Even though all population groups lost income in absolute terms, some were substantially more severely hit by the crisis. The paper examines the effect of the crisis on the population shares, the mean incomes and the level of poverty of various population groups using SILC data for the period 2007-2016. The population is partitioned according to four criteria: socioeconomic group of the household head, presence of unemployed individuals in the household, age of the population member and household type. When “anchored” poverty lines and distribution-sensitive poverty indices are employed the level of poverty rises to incredibly high levels. When the poverty lines used are “relative”, the poverty rate does not change substantially but when distribution-sensitive indices are used the increase in poverty is very substantial. The most interesting results are related to the changes in the structure of poverty. The crisis was associated with a very substantial increase in unemployment. Unemployment protection in Greece was inadequate while there was no “benefit of last resort”. As a result, the relative position of households with unemployed members (and, especially, with unemployed heads) deteriorated sharply, while their contribution to aggregate poverty skyrocketed. Unlike what is often claimed in the Greek public discourse, the relative position of pensioner-headed households improved, although they also experienced a considerable decline in their living standards.
Keywords: D31; I31; I32; 330; Greece; Poverty; Decomposition analysis; Crisis